Sexual Harassment Discourse in News Portal delfi.lt: 2017-2018 - Stundžė, Lijana (Information & Media, 2021)
The definition of sexual harassment is mostly based on its legal regulation and is stated to be one of the forms of discrimination based on sex. However, such designation does not reveal social, psychological, economic, etc. sides of this phenomenon. Therefore, this article pays a lot of attention to the analysis of the phenomenon of sexual harassment, based on the insights of Lithuanian and foreign scientists, examines its forms, causes, consequences, and provides statistical information. As there are no scientific insights into the representation of sexual harassment in the media in Lithuania, research insights from foreign researchers are presented. This article presents an exploratory study of the representation of sexual harassment on the news portal delfi.lt, conducted during the analysis of 2017- 2018 publications. The aim of the article is to analyze the peculiarities of the representation of sexual harassment on the delfi.lt news portal. The research found that the topic of sexual harassment appears on the news portal only in the context of certain events, in this case the #metoo movement; there is a lack of analytical publications that would cover a broader context than the statement of facts; the experience of potential victims is presented as an individual problem.
Keywords: sexual harassment; #metoo; gender equality; representation; news portal; discrimination